Retrieving cloud sensitivity to aerosol using ship emissions in overcast conditions - Quilelli,Correa Rocha Ribeiro R; Gryspeerdt,E; van,Reeuwijk M (Geophysical Research Letters, 2023)
The interaction between aerosols and clouds is one of the major uncertainties in past climate change, affecting the accuracy of future climate projections. Ship tracks, trails left in clouds through the addition of aerosol in the ship exhaust plume, have become a key observational tool for constraining aerosol-cloud interactions. However, manyexpected tracks remain undetected, presenting a significant gap in current knowledge of aerosol forcing. Here we leverage a plume-parcel model to simulate the impact of aerosol dispersion for 2957 cases off California’s coast on cloud droplet number concentration (CDNC) enhancements. Plume-parcel models show a large sensitivity to updraft uncertainties, which are found to be a primary control on track formation. Using these plume-parcel models, updraft values consistent with observed CDNC enhancements are recovered, suggesting that relying solely on cloud-top radiative cooling may overestimate in-cloud updrafts by around 50%, hence overstating the cloud sensitivity to aerosols.